A critical review on core/shell-based nanostructured photocatalysts for improved hydrogen generation. (12th April 2023) - Navakoteswara Rao, V.; Lakshmana Reddy, N.; Preethi, V.; Karthik, Mani; Yu, Yeon-Tae; Yang, Jun Mo; Mamatha Kumari, M.; Shankar, M.V.
Abstract: Photocatalytic water splitting into gaseous hydrogen and oxygen in the presence of semiconductor photocatalysts under a visible spectrum of solar irradiation is one of the most promising processes for plummeting energy demands and environmental pollution. Among the successful photocatalytic materials, the core/shell nanostructures show promising results owing to their fascinating morphology that protects the surface features of the core besides the effective separation of photo-excitons resulting in an enhanced rate of hydrogen production up to 162 mmol h −1 g −1 cat, which is a notable highest value reported in the literature. In this review, we have focused on the basic characteristics of the core-shell structure-based semiconductor photocatalytic systems and their efficient water-splitting reactions under light irradiation. Comprehensive detail on various synthesis methods of core-shell nanostructures, shell thickness-dependent properties, charge-transfer reaction mechanisms, and photocatalytic stability are highlighted in this review. Core-shell nanostructured materials have been extensively used as a photocatalyst, co-catalyst, and by coupling with supporting materials to improve the apparent quantum efficiency up to 45.6%. Besides, important photocatalytic properties that influence the redox reactions i.e., effective exciton separation, the effect of different light sources/wavelengths, surface charge modeling, photocatalytic active sites, and turnover frequency (TOF) have also been focused on and extensively described. Finally, the present and future prospects of the core-shell nanostructured photocatalysts for solar energy conversion into green hydrogen production have been expounded. Graphical abstract: Graphical representation of the core-shell nanostructures preparation and its photocatalytic applications. Image 1 Highlights: Facile synthesis methods for the development of core-shell nanocomposites were highlighted. Effect of synthesis parameters on the photocatalytic performance of the core-shell structures were discussed. Charge transfer mechanism by optimization of shell thickness was explained. Future prospects for the development of core-shell based photocatalysts for hydrogen generation were explored.